Populasi Hama Keong Mas (Pomacea canikulata L.) Dalam Umpan Dan Jebakan Pada Tanaman Padi Sawah (Oryza sativa L.) - Glaudio Lonta; Betsy A. N. Pinaria; Jimmy Rimbing; Marjam M. Toding (Universitas Sam Ratulangi, 2020)
ABSTRACTGolden snail (Pomacea canikulata L.) or also known as mulberry snail is one of the main pestsof rice plants in North Sulawesi, including in the City of Tomohon. This golden snail pest likesyoung rice plants with the intensity of damage varies from 10-100% depending on the level ofpopulation on each land. This pest destroys plants by grating plant tissue and eating it. In responseto help the problems faced by farmers, research has been carried out on the population of thegolden snail pest (Pomaceacaniklata L) in bait and traps on lowland rice plants (Orzya sativa L).The purpose of this study was to determine the effect of the use of papaya leaf baits and watertrench traps on the population of golden snail pests on lowland rice plants. The study wasconducted in Taratara 1 Village, West Tomohoon District, Tomohon City. The duration of thestudy is approximately four months, which took place from March to May 2020. The researchmethod was carried out by quantitative descriptive methods with direct experiments in the field.This experiment uses two lowland rice fields consisting of bait and trap. Observations were madeat the age of plants 21 days after planting, 28 days after planting, and 35 days after planting. Theresults of the research on the treatment of bait using papaya leaves an average of 24.8 individuals/ m2 and on the treatment of traps using an average water trench of 31.4 individuals / m2. Thepopulation of golden snail pests in both treatments decreased from plants aged 21 days afterplanting to 35 days after planting. The age factor in plants can increase the height of golden snailpests. Gold snail can easily attack plants by grating the plant tissue and eating it. Because thestructure of the stems, stems, and leaf blades in the plant is still young. Both treatments contributeto positive results, so that further research is needed by combining bait and trap treatments on alarger scale and can be integrated with other environmentally friendly control methods.